KEANEKARAGAMAN JAMUR MAKROSKOPIS DI JALUR CURUG CIBEUREUM, TAMAN NASIONAL GUNUNG GEDE PANGRANGO - Melly Audina Nurhikmawati; Surti Kurniasih; M. Taufik Awaludin (Universitas Pakuan, 2022)
Gunung Gede Pangrango National Park (GGPNP) is a representative type of mountainous tropical rain forest ecosystem that is rich in biodiversity potential. Research on the diversity of Macrofungi has not been widely, especially in the Cibeureum Waterfall Trail, GGPNP. This study aims to study the diversity of Macrofungi in the Cibeureum Waterfall Trail, GGPNP route. The research was carried out from November 2020 to August 2021. Sampling was carried out by the roaming method. The results of the study of Macrofungi in the Cibeureum Waterfall Trail, GGPNP route obtained 2 phyllum, 9 orders, 22 families and 57 species with a total of 1,360 individuals. The value of the Shannon-Wiener diversity index (H') belongs to the medium category, the evenness index (E) is moderate and the dominance index (D) is low. The abiotic conditions in this area based on the recording of temperature, pH, humidity and light intensity indicate conditions that support the life of Macrofungi in the Cibeureum Waterfall Trail, GGPNP route.